Rasio biomasa dan kelimpahan makrozoobenthos sebagai penduga tingkat pencemaran di teluk jakarta - . Yonvitner; Zulhamsyah Imran (Jurnal Ilmu Pertanian Indonesia, 2006)
The monitoring technic  using  aquatic  organism  as bio indicator was  more  advance.    Monitoring of  water  quality conduct   with  biological indicator among   macrobentic biomass  and  green  mussel  population were  intensively used  by researcher. These research was consider  that  water  quality damage on Jakarta  bay might be identity with biomass analysis approach.   Benthic  organism used as sample  were  macrozoobenthos and green  mussel (Pema viridis).  Water  quality was analysed  using  Fsawb  (Fish and Wild  Life Method) index  from  ott. 1979, then  for  biomass  model  was analysed  by dominant cumulative curve.   Result  of this  research  showed  that  Fsawl index  average  was 64.99, that  its  value  was unappropriate for fishes.   The analysis  of abundance and biomass  comparison index  was tend  to increase  the  density, while the biomass was decrease.   The results  indicate that  water  body  was  already  polluted.  The si:: nificant  impact for  mussel of  pollution was appear on water column at 2 m under of sea level.